2016
DOI: 10.1371/journal.pone.0153751
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Exerts Multiple Regulatory Actions on Human Obese Adipose Tissue Remodeling, Inflammation, Adaptive Thermogenesis and Lipolysis

Abstract: Obesity induces white adipose tissue (WAT) dysfunction characterized by unremitting inflammation and fibrosis, impaired adaptive thermogenesis and increased lipolysis. Prostaglandins (PGs) are powerful lipid mediators that influence the homeostasis of several organs and tissues. The aim of the current study was to explore the regulatory actions of PGs in human omental WAT collected from obese patients undergoing laparoscopic bariatric surgery. In addition to adipocyte hypertrophy, obese WAT showed remarkable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 34 publications
(39 reference statements)
4
63
0
Order By: Relevance
“…To note, PGE 2 in lungs is normally present at much higher concentrations than in plasma, resembling the levels of constitutive COX-2 expression reached in hCOX-2-Tg animals. In line with this, it has been reported that PGE 2 down-regulated the expression of fibrosis-inducing genes in human fat explants from obese individuals as well as the fibrogenic response of differentiated adipocytes to the fibrogenic actions of TGF-β [64].…”
Section: Mcp-1) After MCD Mcp-1 Is a Potent Chemoattractant Mediatorsupporting
confidence: 57%
“…To note, PGE 2 in lungs is normally present at much higher concentrations than in plasma, resembling the levels of constitutive COX-2 expression reached in hCOX-2-Tg animals. In line with this, it has been reported that PGE 2 down-regulated the expression of fibrosis-inducing genes in human fat explants from obese individuals as well as the fibrogenic response of differentiated adipocytes to the fibrogenic actions of TGF-β [64].…”
Section: Mcp-1) After MCD Mcp-1 Is a Potent Chemoattractant Mediatorsupporting
confidence: 57%
“…2D and Supplemental Table 2). As discussed earlier, PGE2 was shown to suppress lipolysis (43)(44)(45)(46). Thus, it is possible that the basal level of PGE2 secreted by adipocytes functions to suppress adipose lipolysis and inflammation, and this process would be reversed somewhat by COX-2 inhibition.…”
Section: Discussionmentioning
confidence: 78%
“…PGD2, PGJ2, d12-PGJ2, 0 -25 M) were also ineffective. It is possible that exogenous PGE2 dampens COX-2-dependent pro-inflammatory signaling by activating the EP4 receptor (43)(44)(45)(46). Thus, we speculate that either a combination of prostaglandins and/or other lipid mediator(s) could be responsible for the COX-2-mediated up-regulation of CCL2/MCP-1.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, isoproterenol-induced adipocyte lipolysis was inhibited by PGE 2 . Collectively, these findings suggest that PGE 2 is a critical regulator of inflammation, fibrosis, and impaired adaptive thermogenesis and lipolysis in human obese visceral WAT [101]. …”
Section: Browning In Humansmentioning
confidence: 99%